Draft Five Year Plan 1980-85 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1980)
Ten inhabited and Seventeen uninhabited coral islands scattered in the Arabian Sea, about 200 to 400 kilometres off the Kerala coast, constitute the Union Territory of Lakshadweep. The islands are identical in structure and formation, rising not more than about 10 metres above the sea. here are shallow lagoons on the western side encircled by coral reefs, beyond which lies the deep sea. On the eastern side, the slope is very abrupt and in some cases the hundred fathom line is found hardly 150 metres from the shore. there are no hills, mountains, lakes or forests.
Planning Department Secretariat Union Territory of Lakshadweep